Piperacillin susceptibility tests by the single-disk agar diffusion technique. - Barry, A L (1979)
Piperacillin is a new semisynthetic penicillin with a spectrum of activity broader than that of carbenicillin or ticarcillin. Studies were performed to establish standards for agar diffusion susceptibility tests with piperacillin disks. Tests with 100-, 150-, and 200-micrograms piperacillin disks and with 100-micrograms carbenicillin disks were evaluated. With both penicillins, 100-micrograms disks were satisfactory, in spite of the fact that piperacillin is a larger molecule and diffuses at a slower rate. With both carbenicillin and piperacillin disks, resistant strains of Staphylococcus aureus produced zones less than or equal to 28 mm and susceptible strains gave zones greater than or equal to 29 mm in diameter. When testing other microorganisms, zone standards of less than or equal to 13 mm for resistant (minimal inhibitory concentration, greater than or equal to 256 micrograms/ml) and greater than or equal to 17 mm for susceptible (minimal inhibitory concentration, less than or equal to 64 micrograms/ml) are recommended for tests with 100-micrograms piperacillin disks. Similar zone standards are currently recommended for carbenicillin and ticarcillin disk tests.